2015
DOI: 10.5713/ajas.15.0028
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chicken Growth Hormones and Insulin-like Growth Factor Gene Polymorphisms with Growth Performance and Carcass Traits in Thai Broilers

Abstract: Molecular marker selection has been an acceptable tool in the acceleration of the genetic response of desired traits to improve production performance in chickens. The crossbreds from commercial parent stock (PS) broilers with four Thai synthetic breeds; Kaen Thong (KT), Khai Mook Esarn (KM), Soi Nin (SN), and Soi Pet (SP) were used to study the association among chicken growth hormones (cGH) and the insulin-like growth factor (IGF-I) genes for growth and carcass traits; for the purpose of developing a suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 26 publications
8
34
1
1
Order By: Relevance
“…This result was in line with Zhang et al (2007) in the Chinese indigenous chicken populations. Different to our findings, Nei et al (2005) and Anh et al (2015) found any associations of this SNP with chicken growth and carcass traits. Nie et al (2005) reported that the AA genotype had positive effects (higher body weight, shank length, and ADG) in a F2 population derived from a cross of a fast-growing line, White Recessive Rock, and a slow-growing line, Xinghua.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This result was in line with Zhang et al (2007) in the Chinese indigenous chicken populations. Different to our findings, Nei et al (2005) and Anh et al (2015) found any associations of this SNP with chicken growth and carcass traits. Nie et al (2005) reported that the AA genotype had positive effects (higher body weight, shank length, and ADG) in a F2 population derived from a cross of a fast-growing line, White Recessive Rock, and a slow-growing line, Xinghua.…”
Section: Discussioncontrasting
confidence: 57%
“…Nie et al (2005) reported that the AA genotype had positive effects (higher body weight, shank length, and ADG) in a F2 population derived from a cross of a fast-growing line, White Recessive Rock, and a slow-growing line, Xinghua. However, Anh et al (2015) found that the AA genotype negatively affected carcass traits (lower body weight and ADG) in Thai broiler chicken. From those various studies, effects of this g.2248G>A GH polymorphism in different chicken breeds generated varied results.…”
Section: Discussionmentioning
confidence: 99%
“…The significant effect of this hormone on laying in chickens has been reported by increasing the number of small follicles in the ovary and also improving the thickness of egg shell [5]. Association study of GH gene polymorphisms and its importance has been confirmed in several studies due to finding significant associations between SNPs and different traits in chickens including body and drumstick weight at 6 weeks of age [6], sexual maturity, egg number and body weight [7], body weight at 4, 6, 8, and 10 weeks of age as well as daily weight gain [2], and also physiological traits including triglyceride content and total serum protein in broiler chickens [8].…”
Section: Growth Hormonementioning
confidence: 99%
“…Applying a candidate gene may result in higher efficiency to detect desired economic traits necessary to increase production and reproduction performances in poultry breeding programs. The growth-correlated genes especially GH and IGF-I genes are regarded as the most promising candidate genes for growth performance and carcass quality traits in chickens [2], necessitating comprehensive genetic probes into the genes responsible for growth and production and evaluating their genetic polymorphisms more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…At present, they have sought alternative food and debris that could contribute and complement the nutritional quality of foods intended for poultry [5-7]. …”
Section: Introductionmentioning
confidence: 99%